Striving for Quality Higher Education: The Quandaries of Academic Planning and Quality Assurance Directorate at the University for Development Studies - Mintah, Grace Asamoah; Agoke, William (MultiTech Publisher, 2024)
The study examined the quandaries of the Directorate of Academic Planning and Quality Assurance (DAPQA) of the University for Development Studies. The study adopted a mixed research approach using purposive sampling to select two staff members from the Directorate and fourteen DAPQA representatives from all the various schools and faculties in the university. The researchers personally administered the questionnaires and conducted the interviews. Descriptive statistics and frequencies were employed to analyze the quantitative data, while the qualitative data were transcribed and coded for easy identification. The study revealed that the directorate is faced with poor cooperation from the university's academic and non-academic staff. It also came to light that there were inadequate personnel and limited office space and funds to carry out their activities. The study, therefore, recommends recruiting qualified staff and continuing workshops for existing staff of the university to appreciate the role of DAPQA and the need to avail themselves whenever needed. Again, university management should organize in-service training for the staff of DAPQA and provide enough office space and funds to carry out its activities.